Effect of Root Pruning on Survival and Early Seedling Growth of Banj Oak (Quercus leucotrichophora, A. Camus) in out Planting - Singh, Virendra; Sah, V. K. (Indian Forester, 2003)
An experiment was undertaken to find out the effect of root pruning on the survival and early growth of Banj oak (Quercus leucotrichophora A. Camus) in out planting. Different treatments revealed that maximum collar diameter and height increment, survival percentage and mean collar diameter and height annual increment were obtained in treatment T2 where roots were pruned to 20 cm. However, light root pruning to a length of 15 cm did not affect the height growth of plants adversely but severe root pruning had significant neg.ative effect on plant growth. The results indicated that roots might be pruned to 20 cm length not only to get the better height growth and survival, though statistically non-significant, but also ease in out planting.